2021
DOI: 10.1136/postgradmedj-2020-139410
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 detection by dogs: from physiology to field application—a review article

Abstract: For years, the dog, man’s best friend, was the most widely employed scent-detector tool for civilian and military purposes. Recently, many studies highlighted the role of canine olfactory ability in the medical field, specifically in detecting different infectious, metabolic and neoplastic conditions. The objective of this literature review is to clarify the rationale behind dog’s ability to detect diseases, to assess the possible application for COVID-19 detection and to discuss the evidence available on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Due to the dog's extraordinary sense of smell, it is most commonly used at airports, especially in the detection of explosives or illegal drugs (Cambau and Poljak, 2020;Else, 2020). Dogs have also been employed in the detection of VOCs associated with human diseases other than COVID-19, such as cancer, diabetic ketoacidosis, hypoglycemia and infections such as CDI, viral diarrhea, and UTI (Sakr et al, 2021). For COVID-19, although the amount of data published so far is limited, additional trials are currently underway in…”
Section: Analysis Of Volatile Organic Compounds (Vocs) In the Exhaled Airmentioning
confidence: 99%
“…Due to the dog's extraordinary sense of smell, it is most commonly used at airports, especially in the detection of explosives or illegal drugs (Cambau and Poljak, 2020;Else, 2020). Dogs have also been employed in the detection of VOCs associated with human diseases other than COVID-19, such as cancer, diabetic ketoacidosis, hypoglycemia and infections such as CDI, viral diarrhea, and UTI (Sakr et al, 2021). For COVID-19, although the amount of data published so far is limited, additional trials are currently underway in…”
Section: Analysis Of Volatile Organic Compounds (Vocs) In the Exhaled Airmentioning
confidence: 99%
“…For years, the dog was the most widely employed scent-detector tool for civilian and military purposes. Recently, many studies highlighted the role of canine olfactory ability in the medical field, specifically in detecting different infectious, metabolic and neoplastic conditions including the coronavirus disease 2019 (COVID-19) (Sakr et al 2021 ). Trained biodetection dogs are already being used for detecting illicit substances and for forensic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…This contamination presents a secondary infection risk to individuals that interact with these surfaces. With respect to the current pandemic, for example, it has been shown that infectious SARS-CoV-2 virions can be recovered hours to days following drying on various objects [ 8 , 9 ]. While fomite-based transmission has proven to be a less significant risk than person-to-person transmission for the existing strains of SARS-CoV-2 [ 10 ], it must still be considered, both to maximize safety under current conditions and to prepare for any future changes in viral transmissibility.…”
Section: Introductionmentioning
confidence: 99%